Natural beekeeping with Ross Conrad [videorecording (DVD)] - Conrad, Ross, 1963- (Chelsea Green Publishing, 2012)
Vermont beekeeper, Ross Conrad, proposes a program of selective breeding and natural hive management. The video presents a comprehensive survey of natural beekeeping methods and challenges.